2018
DOI: 10.1038/s12276-018-0142-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from pluripotent stem cell-derived mesenchymal stem cells acquire a stromal modulatory proteomic pattern during differentiation

Abstract: Mesenchymal stem/stromal cells (MSCs) obtained from pluripotent stem cells (PSCs) constitute an interesting alternative to classical MSCs in regenerative medicine. Among their many mechanisms of action, MSC extracellular vesicles (EVs) are a potential suitable substitute for MSCs in future cell-free-based therapeutic approaches. Unlike cells, EVs do not elicit acute immune rejection, and they can be produced in large quantities and stored until ready to use. Although the therapeutic potential of MSC EVs has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 46 publications
4
35
1
Order By: Relevance
“…Although iPSC‐derived EVs offer advantages in being produced in greater numbers and in stimulating cell metabolism, EVs from MSCs or other cell types that carry distinct cargos may be better suited for other medicinal applications. Recently, a proteomics study illustrated significant differences between human EVs produced by undifferentiated iPSCs and ones produced by iPSC‐derived isogenic MSCs . The former contains more cellular components of active cellular metabolism (consistent with our findings), whereas the latter acquires more stromal cell‐associated modulatory activities .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although iPSC‐derived EVs offer advantages in being produced in greater numbers and in stimulating cell metabolism, EVs from MSCs or other cell types that carry distinct cargos may be better suited for other medicinal applications. Recently, a proteomics study illustrated significant differences between human EVs produced by undifferentiated iPSCs and ones produced by iPSC‐derived isogenic MSCs . The former contains more cellular components of active cellular metabolism (consistent with our findings), whereas the latter acquires more stromal cell‐associated modulatory activities .…”
Section: Discussionsupporting
confidence: 89%
“…Recently, a proteomics study illustrated significant differences between human EVs produced by undifferentiated iPSCs and ones produced by iPSC-derived isogenic MSCs [47]. The former contains more cellular components of active cellular metabolism (consistent with our findings), whereas the latter acquires more stromal cell-associated modulatory activities [47]. One can envision that iPSC-derived EVs may be more efficient in medicinal applications to overcome cellular senescence, whereas EVs produced by various types of MSCs may be better suited to treat stromal disorders of collective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…78 EVs from iMSCs and undifferentiated iPSC-EVs were compared and their cargos were found to differ substantially. 79 While iPSC-EVs enclose proteins that modulate RNA and miRNA stability and protein sorting, iMSC-EVs enriched proteins that organize ECM and influence cell-substrate adhesions.…”
Section: Evs/exosomes Secreted By Ipsc-derived Mesoderm Cellsmentioning
confidence: 99%
“…La Greca et al identified 560 proteins from pluripotent stem cell-derived extracellular vesicles through proteomic analysis. Extracellular vesicles shared 37.32% of the proteins with parental cells and enriched with molecules relevant with immunity, extracellular matrix, and cell adhesion [39]. Otero-Ortega et al studied the proteomic signature of rat adipose-derived MSC-EVs in an experimental animal model of subcortical stroke.…”
Section: Discussionmentioning
confidence: 99%